A New Tool for Faster Construction of Marine Biotechnology Collaborative Networks - Rotter, Ana; Gaudêncio, Susana P.; Klun, Katja; Macher, Jan-Niklas; Thomas, Olivier P.; Deniz, Irem; Edwards, Christine; Grigalionyte-Bembič, Ernesta; Ljubešić, Zrinka; Robbens, Johan; Varese, Giovanna Cristina; Vasquez, Marlen I. (Frontiers in Marine Science, 2021)
The increasing and rapid development in technologies, infrastructure, computational power, data availability and information flow has enabled rapid scientific advances. These entail transdisciplinary collaborations that maximize sharing of data and knowledge and, consequently, results and possible technology transfer. However, in emerging scientific fields it is sometimes difficult to provide all necessary expertise within existing collaborative circles. This is especially true for marine biotechnology that directly addresses global societal challenges. This article describes the creation of a platform for formation of short or mid-term collaborative networks in marine biotechnology. The platform (https://www.ocean4biotech.eu/map/) enables experts (researchers and members of the marine biotechnology community in general) to have the possibility to showcase their expertise to be integrated into new collaborations/consortia on the one hand, or to use it as a search tool to complement the expertise in planned/running collaborations, on the other. The platform was created within the Ocean4Biotech (European transdisciplinary networking platform for marine biotechnology) Action, funded under the framework of the European Cooperation in Science and Technology (COST). To build the platform, an inquiry was developed to identify experts in marine biotechnology and its adjunct fields, to define their expertise, to highlight their infrastructures and facilities and to pinpoint the main bottlenecks in this field. The inquiry was open to all experts in the broad field of marine biotechnology, including non-members of the consortium. The inquiry (https://ee.kobotoolbox.org/single/UKVsBNtD) remains open for additional expertise and the resulting interactive map can be used as a display and search tool for establishing new collaborations.